PTU-098 Optimising access to best-practice care in primary biliary cholangitis across the UK. (8th June 2018) - Gwynn, Simon; Barnabas, Ashley; Brew, Iain; Corless, Lynsey; Ross, Valerie; Warren, Tim; Smith, BC; Fairclough, Sarah
Abstract : Introduction: Systematic review of the implementation of Integrated Care Pathways (ICPs) has shown that they can effectively support proactive care management, adherence to guidelines, improve equity of service access and reduce variance in practice. A multidisciplinary team applied this process to the case management of patients with Primary Biliary Cholangitis (PBC) in order to support the development of a defined standard of case management, based on current evidence and acknowledged best practice. Methods: Using a structured process of facilitation and project management, this multidisciplinary working group of specialists has developed an ICP for PBC in accordance with ICPAT standards and current best-practice thinking. Results: The ICP forms comprise a streamlined and easy to implement solution for structuring each consultation along the patient pathway. The forms support each activity undertaken around the patient as they progress along the pathway. The PBC ICP comprises: A process map defining the consultation flow along the patient journey A set of forms for use at each consultation, ensuring that appropriate assessments and interventions are performed according to the evidence base and best practice A comprehensive support booklet, containing the full evidence base for PBC management and instructions supporting implementation of the ICP This ICP is available in Word format so that it may be easily modified and implemented by clinical teams across the UK. Conclusions: Adoption of the ICP by PBC teams across the UK may facilitate robust implementation of best practice and improve equity of service provision. In addition, the ICP forms are designed to encourage clinical teams to support each part of the patient journey, including those where specialist resource is not required. This group proposes that the PBC ICP offers a useful solution to optimising case management within the challenging economic constraints faced by the NHS.